Positive end-expiratory pressure induced changes in airway driving pressure in mechanically ventilated COVID-19 Acute Respiratory Distress Syndrome patients - Mônica Rodrigues da Cruz; Luciana Moisés Camilo; Tiago Batista da Costa Xavier; Gabriel Casulari da Motta Ribeiro; Denise Machado Medeiros; Luís Felipe da Fonseca Reis; Bruno Leonardo da Silva Guimarães; André Miguel Japiassú; Alysson Roncally Silva Carvalho (Critical Care, 2023)
Abstract Background The profile of changes in airway driving pressure (dPaw) induced by positive-end expiratory pressure (PEEP) might aid for individualized protective ventilation. Our aim was to describe the dPaw versus PEEP curves behavior in ARDS from COVID-19 patients. Methods Patients admitted in three hospitals were ventilated with fraction of inspired oxygen (FiO2) and PEEP initially adjusted by oxygenation-based table. Thereafter, PEEP was reduced from 20 until 6 cmH2O while dPaw was stepwise recorded and the lowest PEEP that minimized dPaw (PEEPmin_dPaw) was assessed. Each dPaw vs PEEP curve was classified as J-shaped, inverted-J-shaped, or U-shaped according to the difference between the minimum dPaw and the dPaw at the lowest and highest PEEP. In one hospital, hyperdistention and collapse at each PEEP were assessed by electrical impedance tomography (EIT). Results 184 patients (41 including EIT) were studied. 126 patients (68%) exhibited a J-shaped dPaw vs PEEP profile (PEEPmin_dPaw of 7.5 ± 1.9 cmH2O). 40 patients (22%) presented a U (PEEPmin_dPaw of 12.2 ± 2.6 cmH2O) and 18 (10%) an inverted-J profile (PEEPmin_dPaw of 14,6 ± 2.3 cmH2O). Patients with inverted-J profiles had significant higher body mass index (BMI) and lower baseline partial pressure of arterial oxygen/FiO2 ratio. PEEPmin_dPaw was associated with lower fractions of both alveolar collapse and hyperinflation. Conclusions A PEEP adjustment procedure based on PEEP-induced changes in dPaw is feasible and may aid in individualized PEEP for protective ventilation. The PEEP required to minimize driving pressure was influenced by BMI and was low in the majority of patients.